THE POWER OF CONTINUOUS LEARNING: WHY WE SHOULD NEVER STOP EDUCATING OURSELVES - Bobasheva Mohinur Ismonbek qizi (TADQIQOTLAR, 2026)
Abstract. Continuous learning plays a significant role in human life and has a strong influence on personal development, professional adaptability, and cognitive well- being. Lifelong education is based on curiosity, self-discipline, and the desire for constant self-improvement. It helps individuals overcome economic shifts, technological advancements, and professional stagnation. This article discusses the importance of continuous learning in our life, its psychological and neurological benefits, and its role in shaping a resilient and positive personality. The paper also highlights how constant education contributes to mental health, fosters workplace innovation, and strengthens individual adaptability in a modern, fast-paced society.